High frame rate photoacoustic imaging at 7000 frames per second using clinical ultrasound system - Sivasubramanian, Kathyayini (2016)
Photoacoustic tomography, a hybrid imaging modality combining optical and ultrasound imaging, is gaining attention in the field of medical imaging. Typically, a Q-switched Nd:YAG laser is used to excite the tissue and generate photoacoustic signals. But, such photoacoustic imaging systems are difficult to translate into clinical applications owing to their high cost, bulky size often requiring an optical table to house such lasers. Moreover, the low pulse repetition rate of few tens of hertz prevents them from being used in high frame rate photoacoustic imaging. In this work, we have demonstrated up to 7000 Hz photoacoustic imaging (B-mode) and measured the flow rate of a fast moving object. We used a ~140 nanosecond pulsed laser diode as an excitation source and a clinical ultrasound imaging system to capture and display the photoacoustic images. The excitation laser is ~803 nm in wavelength with ~1.4 mJ energy per pulse. So far, the reported 2-dimensional photoacoustic B-scan imaging is only a few tens of frames per second using a clinical ultrasound system. Therefore, this is the first report on 2-dimensional photoacoustic B-scan imaging with 7000 frames per second. We have demonstrated phantom imaging to view and measure the flow rate of ink solution inside a tube. This fast photoacoustic imaging can be useful for various clinical applications including cardiac related problems, where the blood flow rate is quite high, or other dynamic studies.